The Socioeconomic and Ethnic Segregation of Living Conditions in Copenhagen - Iver Hornemann Møller; Jørgen Elm Larsen (Revista Crítica de Ciências Sociais, 2015)
The aim of this article is to analyze the discrepancies between certain aspects of living conditions of ethnic Danes and immigrants in Copenhagen. Copenhagen is quite prosperous and fares well in the globalized economy but is at the same time experiencing increasing poverty and ethnic segregation. Differences in income have increased spatial segregation in Copenhagen in terms of housing and education. This segregation is most visible in relation to highly educated Danes and immigrants from non-Western countries. The article first examines poverty at household level and its spatial dimensions. Secondly, it considers other living conditions (for example social networks). Thirdly, it explores immigrants’ experiences of, among other things, education, employment and citizenship. It concludes that social cohesion in Copenhagen may be threatened if this segregation continues.